Comparison of the Impact of Structural Family Therapy and Cognitive Behavioral Therapy on the Marital Satisfaction of Couples Seeking Divorce in Minoodasht in 1401-1402 - Mirdousti, Seyed Gholamreza; Shariatnia, Kazem; Bakhtiari Saeed, Bahram; Asadi, Javanshir; Azizi Ziabari, Leyla Sadat (Shahroud Journal of Medical Sciences, 2025)
Background: Marital conflict is a major predictor of divorce, often resulting in emotional distress and reduced relationship satisfaction. Cognitive-Behavioral Therapy (CBT) and Structural Family Therapy (SFT) are widely used interventions to improve marital relationships. This study aimed to assess and compare the effectiveness of CBT and SFT in enhancing marital satisfaction among conflicted couples seeking divorce.Methods: Thirty couples referred to a judiciary counseling center in Minoodasht who met the inclusion criteria participated in this quasi-experimental study with a pretest–posttest design and two intervention groups. The ENRICH Marital Satisfaction Scale was administered before and after the interventions. Each group received eight sessions of either CBT or Minuchin’s SFT. Changes in marital satisfaction scores were analyzed to evaluate the effects of both therapies.Results: Both groups showed significant improvements in marital satisfaction after the interventions. However, there was no statistically significant difference between the two approaches, indicating that CBT and SFT were comparably effective in improving marital satisfaction.Conclusions: CBT and SFT both significantly and similarly enhance marital satisfaction among conflicted couples seeking divorce. These findings support the application of either approach in counseling settings for couples experiencing marital distress.